“Unity, Cohesion, Vitality” from Horasan to Anatolia; Social Cohesion in the Sultans of Saz and Word - Akın, Erdem; Üstündağ, Kader (Journal of Alevism-Bektashism Studies, 2024)
Hünkâr Hacı Bektaş Veli, a Turkish-Islamic mystic born within the historical borders of Khorasan and who settled in Anatolia, is a messenger of friendship and love. Poets who followed his path and grew within the Alevi-Bektashi belief system, writing poems on a wide variety of topics, are notable for the strong social references in their works. Known as the “sultans of saz and word,” they adopted the tradition of minstrel and folk poetry from a young age, infusing their works with the Alevi-Bektashi faith and culture. They emphasized messages of social cohesion and unity, standing against division and segregation.This study highlights how the teachings of Hacı Bektaş Veli and the Alevi-Bektashi poetic tradition provide a robust model for social integration from multiple perspectives. Utilizing the documentation analysis technique, the study includes examples from poems to focus on the role of minstrels in social cohesion. The findings underscore the strong social cohesion aspect of the poems by Alevi-Bektashi poets, who represent the vibrancy and prevalence of the minstrel tradition among follower communities. These poets, who did not remain indifferent to the issues of unity and integration within their society, emphasized themes of unity, equality, brotherhood, peace, and the absence of division based on religion, sect, and race in their poems.These poems not only contribute to social integration but also play a significant role in ensuring the intergenerational continuity of the Alevi-Bektashi poetic tradition. Thus, the legacy of Hacı Bektaş Veli and the works of Alevi-Bektashi poets serve as universal, timeless, inclusive, and effective tools for reducing polarization. While the revered personality of Hünkar himself is a factor that strengthens and sustains social solidarity, the Alevi-Bektashi poetic tradition retains its relevance in today’s world, continuing to promote solidarity and integration within society.
Keywords: Haci Bektas Veli; Alevi-Bektasi Poetry Tradition; Minstrelsy; Zakirlik; Social cohesion